2017
DOI: 10.1159/000457877
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of p62 to Phenotype Transition of Coronary Arterial Myocytes with Defective Autophagy

Abstract: Background: Autophagy disorder contributes to dedifferentiation of arterial smooth muscle cells, but the mechanisms are poorly understood. Here, we sought to investigate the role of scaffolding adaptor p62/SQSTM1 (p62) in phenotype switching of mouse coronary arterial myocytes (CAMs) induced by CD38 gene deficiency or lysosomal dysfunction which blocks autophagic flux in the cells. Methods: Protein expression was measured by western blot analysis and immunofluorescent staining. Cell cycle and proliferation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Recent studies showed that the mammalian target of rapamycin complex (mTORC) signaling on late endosomes (LEs)/lysosomes may control cargo selection, membrane biogenesis, and lysosome trafficking in lysosomal degradation pathways, 22 which is fine controlled by sphingolipids, CER, and sphingosine‐1‐phosphate (S1P) 23 . This sphingolipid‐regulated mTORC signaling has been reported to be involved in VC, 24 which may be a crucial molecular mechanism responsible for the development of calcification of atheromatous plaques and even in arterial medial layer due to lysosome dysfunction that we observed recently 25‐27 . In fro / fro (N‐SMase2 −/− ) fibroblasts, study anticipated that N‐SMase2 and CER are the important mediators in the regulation of hyaluronan synthesis, via microdomains and the Akt/mTOR pathway 28 .…”
Section: Introductionsupporting
confidence: 51%
“…Recent studies showed that the mammalian target of rapamycin complex (mTORC) signaling on late endosomes (LEs)/lysosomes may control cargo selection, membrane biogenesis, and lysosome trafficking in lysosomal degradation pathways, 22 which is fine controlled by sphingolipids, CER, and sphingosine‐1‐phosphate (S1P) 23 . This sphingolipid‐regulated mTORC signaling has been reported to be involved in VC, 24 which may be a crucial molecular mechanism responsible for the development of calcification of atheromatous plaques and even in arterial medial layer due to lysosome dysfunction that we observed recently 25‐27 . In fro / fro (N‐SMase2 −/− ) fibroblasts, study anticipated that N‐SMase2 and CER are the important mediators in the regulation of hyaluronan synthesis, via microdomains and the Akt/mTOR pathway 28 .…”
Section: Introductionsupporting
confidence: 51%
“…One of the more important findings in the present study is that the actions of GDF11 in the control of CASMC differentiation and counteraction on phenotypic transition upon pathological stimulations are associated with its regulation of autophagy in these cells, in particular, the autophagic flux process. It is well known that autophagy is a cellular homeostatic process that degrades unwanted or dysfunctional components of cells for recycling or removal (2,10). Defective autophagy promotes the proliferation and dedifferentiation of VSMCs, contributing to the generation and deterioration of atherosclerosis (8,19).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that CD38 regulates lysosome trafficking and fusion to autophagosomes and thus determines the fate of the autophagosome controlling autophagic flux in VSMCs (44,51). CD38 deficiency (CD38 Ϫ/Ϫ ) led to autophagosome accumulation, which promoted a phenotype transition and proliferation of coronary VSMCs by accelerating cell cycle progression through the G 2 /M phase (2). Other lysosome function inhibitors or disruptors were also found to cause autophagosome accumulation and phenotypic transition of coronary VSMCs to be more dedifferentiated or degenerative (3).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the overexpression of CD38 is correlated with many human diseases. It has been reported that CD38 deficiency increased autophagy [52], while autophagy is closely related to cardiac diseases. In the present study, we found that the intracellular concentration of NAD + in hearts from CD38 deficient mice was 177 folds higher than wild type mice, which was consistent with our previous study in CD38 knockout or knockdown models [7,53].…”
Section: Discussionmentioning
confidence: 99%